Two new species of Chrysotus Meigen (Diptera, Dolichopodidae) from Siberia, with a key to the Siberian species - Negrobov, Oleg P.; Barkalov, Anatolij V.; Selivanova, Olga V. (Zootaxa, 2014)
Two new species from the southern tundra of the Taimyr Peninsula (Russia) are described. Chrysotus tricaudatus Negrobov, Barkalov & Selivanova sp. nov. is similar to C. albibarbus Loew, but can be distinguished by its brown palpus with black setae, yellow hind tibia and base of hind tarsus, and features of the male genitalia. Chrysotus komovi Negrobov, Barkalov & Selivanova sp. nov. is similar to C. obscuripes Zetterstedt, but can be distinguished by features of the male genitalia. A key to all Siberian species of the genus is also presented along with figures of diagnostic morphological characters.